Glioblastoma: Molecular Mechanisms of Pathogenesis and Current Therapeutic Strategies - Ray, Swapan K. (Springer New York : Imprint: Springer, 2010)
Glioblastoma, the deadliest of all primary brain tumors, is heterogenic and has very complex pathology and multiple mechanisms of cell proliferation and growth. This book describes all the latest concepts about the molecular mechanisms of pathogenesis of glioblastoma and new therapeutic opportunities. The contributors to this book include basic scientists and clinicians, who are experts in the field, and dedicated investigators in finding novel strategies for treatment of glioblastoma. It is important for us to know the strategies we have accumulated so far for the management of this malignancy so that we can make further attempts to explore unknown avenues to combat it completely in the near future.